2014
DOI: 10.1103/physrevb.90.045116
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of single-crystallineNdO0.5F0.5BiS2studied by angle-resolved photoemission spectroscopy

Abstract: BiS 2 is a new layered superconductor. We have studied the low-lying electronic structure of a single crystalline NdO 0.5 F 0.5 BiS 2 superconductor, whose superconducting transition temperature is 4.87K, with angle-resolved photoemission spectroscopy. The Fermi surface consists of two small electron pockets around the X point and shows little warping along the k z direction. Our results demonstrate the multi-band and twodimensional nature of the electronic structure. The good agreement between the photoemissi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
40
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 27 publications
12
40
2
Order By: Relevance
“…In addition, possible triplet paring and weak topological superconductivity were suggested based on renormalization-group numerical calculation [16], but this mechanism is still much debated. Moreover, the experiments on the NdO 0.5 F 0.5 BiS 2 single crystals also reveal interesting discoveries concerning the SC mechanisms in this new system [17][18][19][20][21].…”
mentioning
confidence: 99%
“…In addition, possible triplet paring and weak topological superconductivity were suggested based on renormalization-group numerical calculation [16], but this mechanism is still much debated. Moreover, the experiments on the NdO 0.5 F 0.5 BiS 2 single crystals also reveal interesting discoveries concerning the SC mechanisms in this new system [17][18][19][20][21].…”
mentioning
confidence: 99%
“…Very recently, an x-ray photoemission spectroscopy (XPS) study on LaO 1−x F x BiS 2 [24] and angle-resolved photoemission spectroscopy (ARPES) studies on NdO 1−x F x BiS 2 [25,26] have revealed that there is an overall agreement between the band-structure calculations and the experimental band dispersions and Fermi surfaces. However, the XPS spectral weight near the Fermi level (E F ) appears to disagree with the calculations, and the disagreement emphasizes the importance of the electron-electron and/or electron-phonon interactions [24].…”
Section: Introductionmentioning
confidence: 84%
“…The possible polaron correlation effect is also suggested by the peculiar temperature dependence reported in the ARPES study by Zeng et al [25]. On the other hand, the ARPES study by Ye et al indicates rather weak electron correlations [26]. In addition, an optical spectroscopy study by Wang et al excludes strong electron/polaron correlations [27].…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The maximum T c that can be achieved in the weak coupling limit is ∼20 K. [6,14] The BiS 2 systems are phononic superconductors [15,16] with an electron-phonon coupling constant ∼0.8 indicating strong coupling. [17,18] The experimental results from magnetic penetration depth, muon spin rotation spectroscopy and angle-resolved photoemission spectroscopy (ARPES) also support conventional BCS superconductivity mediated by electron phonon coupling [19][20][21]. However, scanning tunneling spectroscopy (STS) measurements show two superconducting gaps exist in NdO 1−x F x BiS 2 .…”
Section: Introductionmentioning
confidence: 99%